A Thematic Analysis of Indigenous Students’ Experiences with Indigenization at a Canadian Post-secondary Institution: Paradoxes, Potential, and Moving Forward Together - Efimoff, Iloradanon (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2022)
Indigenization is a relatively new phenomenon in Canada. It is a broad concept that includes everything from changing physical spaces to challenging Western epistemologies and the status quo. In this study, I describe nine Indigenous students’ experiences with Indigenization at the University of Saskatchewan. Students were impacted both positively and negatively by their engagement: They described both opportunities borne of engagement with Indigenization and detriments such as exhaustion and lack of basic needs. In terms of methods to Indigenize, the participants described the importance of representation, centring Indigenous values and knowledges, and creating communities that can Indigenize. I end the paper with four policy recommendations for post-secondary institutions interested in Indigenization.